Test of precast pre-stressed beam-to-column joint with damage-free reinforced concrete slab. (1st May 2020) - Wang, Haishen; Barbagallo, Francesca; Pan, Peng
Highlights: A beam-to-slab connection is developed for precast pre-stressed beam-to-column joint. The seismic response of the proposed joint is investigated by experimental tests. The performance of the proposed joint is compared to that of a conventional joint. The proposed joint provides better energy dissipation and self-centering capacity. The proposed joint preserves the slab from damage under large drift ratio. The width of slab cracks is controlled below 0.4 mm and slab rebars remain elastic. Abstract: Conventional and pre-stressed precast reinforced concrete slabs are usually affected by severe damage induced by earthquakes. The repair of damaged slabs may compromise the resilience capacity of the structure. To overcome this drawback, this study introduces a new type of precast pre-stressed beam-to-column joint that prevents slab damage even under severe earthquakes. The connection between the slab and beam was made by using uplift-restricted slip-free rebar; contact surfaces between beam, column, and slab were smoothed to minimize interface friction. Deformation patterns of the proposed joint were analytically investigated and compared with those of a beam-to-column joint with conventional connection with the slab. Two 0.6-scale specimens were designed, the first with conventional beam–slab connection and the second with the proposed one, and tested under quasi-static conditions. Enhanced seismic behavior of the developed joint was demonstrated by results of seismic performance of these two specimens in terms of crack development, maximum bearing capacity, energy dissipation, and rebar strain. The proposed connection prevented damage in the slab up to a drift ratio equal to 1/18.